Impactos do BRT Transcarioca : uma análise das transformações urbanas em Vicente de Carvalho - Silva, Giuliana Lopes Moreira da (2025)
This research analyzes the impact of the BRT TransCarioca in the Vicente de Carvalho neighborhood, investigating how its implementation has transformed urban mobility, real estate appreciation, and local social dynamics. The study examines to what extent the system has improved population mobility, reduced travel times, and promoted integration between different transport modes, with a particular focus on the quality of life of residents in peripheral areas. The adopted methodology combines bibliographic review, documentary analysis, and interviews with users. The case study in the Vicente de Carvalho neighborhood enabled a detailed investigation of changes in land use, real estate appreciation, and alterations in territorial organization following the implementation of the BRT. The results indicate that, despite improving connectivity between different regions of the city, the system has faced significant challenges, such as overcrowding, operational failures, inadequate maintenance, and insufficient integration with other transport modes. Furthermore, real estate appreciation in some areas has led to the displacement of low-income residents, intensifying socio-spatial segregation and making access to essential services more difficult for vulnerable populations. The BRT infrastructure has brought development to some regions, encouraging new businesses and urban improvements. However, the lack of integrated planning with housing and social policies has created inequalities in access to transportation. The research concludes that, although the BRT has potential as a sustainable mobility alternative, its implementation has revealed flaws in management and urban planning. To make this model more efficient and inclusive, strategies for better maintenance, integration with other transport modes, and mitigation of negative impacts on vulnerable populations are necessary. This study contributes to the debate on urban mobility and public policies, suggesting guidelines for more equitable and accessible transportation.